Agricultural exit problems: Causes and consequences - Headey, Derek D.; Bezemer, Dirk J; Hazell, Peter B. R. (International Food Policy Research Institute, 2008)
Contrary to conventional economic theories, the relationship between income growth and the share of the population within the rural or agricultural sector is extremely diverse, even among regions starting from similar levels of development, such as Asia and Africa. The pattern in developing Asia is characterized by fast growth and slow urbanization, primarily as the result of labor-intensive agricultural growth and strong farm?nonfarm linkages. But for all its success to date, Asia appears to be increasingly vulnerable to rising inequality and jobless growth patterns. Africa presents a divergent pattern of slow growth with rapid urbanization stemming from urban-biased policies, low rural population density, and high rates of population growth. But whereas Africa?s path of urbanization without growth presents problems like unemployment, congestion, and food-price inflation, it may also provide new development possibilities through greater political empowerment, lower fertility rates, and agglomeration externalities. The paper concludes with a discussion of how development strategies can address these agricultural exit problems.